Real-time detection of focal position of workpiece surface during laser processing using diffractive beam samplers. (November 2016) - Cao, Binh Xuan; Hoang, PhuongLe; Ahn, Sanghoon; Kim, Jeng-o; Sohn, Hyonkee; Noh, Jiwhan
Abstract: The real-time fabrication of microgrooves on a curved surface using a laser beam, without preprogramming their shapes into the machining instructions, is a major challenge in laser processing owing to limitations associated with the real-time detection of the focal position. A new approach using a sampled fraction of the beam from a diffractive beam sampler (DBS) is therefore presented in order to overcome this limitation. By considering the sampled fraction of the beam an analysis of the results allows for precise positioning of the specimen for focal-point identification. This allows for the determination of the focus for a broad variety of laser types and laser powers, thereby providing stringent focusing conditions with high numerical apertures. This approach is easy to implement, inexpensive, independent of the roughness or granularity of the workpieces, and more importantly does not require auxiliary lasers and displacement sensors for real-time measurement during the fabrication process. Highlights: A novel method for the real-time detection of the focal position is proposed. We use a beam splitter, a charge-coupled device, and a diffractive beam sampler. The focus-determination system is based on the sampled separation of a beam. This technique offers stringent focusing conditions with high numerical apertures. This method can be implemented with a variety of lasers and a workpiece surfaces.